Principles of ownership and the transmission of knowledge in contemporary dance and Irish traditional music: Social norms and legal contexts. Issue 2 (16th May 2022) - Leach, James
Abstract: Drawing on the contributions to this special issue, this article offers a synthetic description of the principles of ownership, sharing, and reward that guide and stimulate the creative practices of contemporary dance. Irish traditional music is also considered. The article aims to contextualize creative practices within a series of concerns around the protection and perpetuation of valuable cultural and artistic practices. This contextualization establishes the relevance and interest of the contemporary dance for other domains and attends to the contemporary conditions of cultural production, including those of intellectual property law, commercialization, and community/commons formation. I show how this work offers an illuminating model of social process in which value created in common is linked – through reputation, attribution, recognition, and innovation – to people, without private property becoming the dominant mode of ownership.